Lewis acid molten salts prepared Ti3C2Cl2 MXenes assembling with g-C3N4 nanosheets for enhanced photocatalytic H2 evolution. Issue 8 (15th April 2023) - Zhou, Hongmiao; Tian, Jiayi; Wang, Ruoyu; Zhan, Difu; Liu, Peng; Chen, Ruolin; Huang, Yizhong; Liu, Zhifeng; Han, Changcun
Abstract: Photocatalytic hydrogen (H2 ) evolution is expected to be a promising approach to generating a clean energy source (H2 ) with low carbon emissions, which is vital to solving environmental degradation and energy shortages. The critical challenge to designing highly efficient photocatalysts is the fast recombination of photo-generated carriers; thus, we select Ti3 C2 Cl2 MXene with excellent metal characteristics to serve as a co-catalyst and combine with g-C3 N4 . The Ti3 C2 Cl2 /g-C3 N4 composites exhibit an enhanced photocatalytic hydrogen evolution activity (maximum 155.9 μmol h −1 ) while they hardly perform photocatalytic activities. The photoluminescence (PL) spectra shows that Ti3 C2 Cl2 MXenes help boost the separation of photo-generated carriers of g-C3 N4 and finally strengthen the photocatalytic hydrogen evolution performance. The ultraviolet–visible (UV–vis) spectra illustrate that composites perform a strengthened light absorption, which fits well with the results in the hydrogen evolution experiment. Thus, we fabricated a highly efficient photocatalyst through a safer molten salt approach without hydrofluoric acid (HF). We believe this work will offer a safer approach to manufacturing catalysts decorated with MXenes for highly efficient photocatalytic H2 evolution.